Perceived-teacher presenteeism scale: A scale development study - Uslukaya, Alper; Demirtas, Zulfu; Alanoglu, Muslim (Izzet Kara, 2022)
This study aims to develop and test the reliability and validity of a multiitem teachers' perceived presenteeism behavior scale. For this, first of all, a semistructured interview form was applied to 57 teachers, an item pool was formed for the presenteeism scale with the data obtained, and the draft form of the scale was prepared in line with the expert opinions. Then, the draft scale form was applied to 382 teachers, and exploratory factor analysis was performed with the data obtained. As a result of the analysis, a three-dimensional scale structure consisting of 14 items was obtained. Data were collected from 303 teachers to confirm this structure, and the three-factors scale structure was confirmed based on acceptable fit values with confirmatory factor analysis. It was determined that the validated second-order three-factor model provided convergent and discriminant validity criteria. The measurement invariance of the scale according to gender, marital status, and age groups was tested, and it was observed that the same structure was measured in different groups. Cronbach Alpha internal consistency coefficient and composite reliability values showed that sufficient reliability values were achieved for the scale. Finally, the test-retest performed to test its stability showed that the scale was stable. Thus, it was concluded that the scale is valid and reliable with sufficient conditions to measure the teachers' perceptions of presenteeism.
Keywords: Factorization; Measurement invariance; Presenteeism; Scale development; Teacher presenteeism